The Quick Sepsis-Related Organ Failure Assessment Score Is Prognostic of Pancreatitis Severity in Patients With Alcohol-Induced Pancreatitis. Issue 6 (July 2022) - Wagner, Jason; Hernández Blanco, Yllen Y.; Yu, Abraham; Garcia-Rodriguez, Victor; Mohajir, Wasay; Goodman, Colin; DuPont, Andrew W.; Cash, Brooks D.; Farooq, Ahmad
Abstract : Objectives: The aim of this study was to determine if the quick Sepsis-Related Organ Failure Assessment (qSOFA) score assessed at and 48 hours after admission is prognostic for alcohol-induced acute pancreatitis (AAP) severity. Methods: This is a retrospective cohort review study of 161 patients admitted to a single academic hospital in Houston, TX, with the diagnosis of AAP. Receiver operator characteristics analysis and logistic regression were used to assess the diagnostic accuracy and prognostic ability of the qSOFA score. Results: A qSOFA score of 2 or higher at and 48 hours after admission had a specificity of 94% or greater and sensitivity of 33% or higher for pancreatitis severity and need for intensive care admission, intubation, or vasopressors. The qSOFA score at and 48 hours after admission was prognostic of intensive care unit admission by an adjusted odds ratio of 48.5 (95% confidence interval [CI], 6.4–1013.3; P < 0.001) and 18.8 (95% CI, 2.2–467.3; P < 0.05), respectively. The qSOFA score at admission was prognostic of severe pancreatitis by an adjusted odds ratio of 35.3 (95% CI, 7.2–224.3; P < 0.001). Conclusions: A qSOFA score of 2 or higher is highly specific and prognostic of multiple clinical outcomes both at and 48 hours after admission in patients with AAP.